2013
DOI: 10.1007/s10238-013-0238-5
|View full text |Cite
|
Sign up to set email alerts
|

Comparative characteristics of endothelial-like cells derived from human adipose mesenchymal stem cells and umbilical cord blood-derived endothelial cells

Abstract: Adult peripheral blood contains a limited number of endothelial progenitor cells that can be isolated for treatment of ischemic diseases. The adipose tissue became an interesting source of stem cells for regenerative medicine. This study aimed to investigate the phenotype of cells obtained by culturing adipose-derived mesenchymal stem cells (ad-MSCs) in the presence of endothelial growth supplements compared to endothelial cells obtained from umbilical cord blood (UCB). Passage 3 ad-MSCs and mononuclear layer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…Another promising cell source is adult mesenchymal stem cells 25 . The hASCs derived from mesoderm differentiate into multiple lineages 17 18 19 20 . Cao et al 26 demonstrated that hASCs showed morphology and function similar to that of endothelial cells when cultured in media containing VEGF and bFGF.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another promising cell source is adult mesenchymal stem cells 25 . The hASCs derived from mesoderm differentiate into multiple lineages 17 18 19 20 . Cao et al 26 demonstrated that hASCs showed morphology and function similar to that of endothelial cells when cultured in media containing VEGF and bFGF.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, hASCs have demonstrated the potential for differentiation into multiple cell lineages, including osteocytes, chondrocytes, smooth muscle cells and endothelial cells 7 8 9 10 11 12 13 14 15 16 17 18 19 20 . In addition, hASCs are easier to obtain and exhibit lower donor-site morbidity.…”
mentioning
confidence: 99%
“…Various studies that have used BMSCs transplantation to treat SCI have demonstrated that they can differentiate into functional neurons or glias, while secreting neurotrophic factors that modulate local inflammation, thereby creating a microenvironment that facilitates nerve regeneration and is conducive to functional recovery (Cui et al, ; Kim et al, ; Liu et al, ; Roh et al, ; Jarocha et al, ). Besides the bone marrow, BMSCs can be obtained from umbilical cord and peripheral blood and fat tissue, and the source of BMSCs dictate their differentiation potential (Gaafar et al, ; Pang et al, ; Pham et al, ). Implantation of BMSCs‐derived cells has been reported to elicit de novo neurogenesis and functional recovery in a nonhuman primate model of spinal cord injury (Deng et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Primary ADSCs also partly expressed CD34 and CD105, which showed that these ADSCs were comprised of heterogeneous cell populations. CD34 was quiescence stem cell and endothelial cell marker [40] . Usually, CD105 expression was relatively low on the freshly isolated ADSCs.…”
Section: Discussionmentioning
confidence: 99%